2018
DOI: 10.21037/jovs.2018.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Adult pulmonary intralobar sequestrations: changes in the surgical management

Abstract: Background: Until now, the traditional procedure to treat intralobar pulmonary sequestration (ILS) in adults has been a lobectomy performed by open chest surgery. We have reviewed our data to determine whether the surgical management of these lesions has evolved over the last years. Methods:We retrospectively reviewed the records of patients who were operated on for an ILS by either posterolateral thoracotomy (PLT group), or by thoracoscopy (TS group) between 2000 and 2016.Results: Eighteen patients were opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Left basilar VATS segmentectomy for intra lobar pulmonary sequestration using indocyanine green for identification of the intersegmental plane: a case report entire lobe that is affected and a segmentectomy should be considered (3). I present the following case in accordance with the CARE reporting checklist (available at http:// dx.doi.org/10.21037/jovs-21-21).…”
Section: Case Reportmentioning
confidence: 99%
“…Left basilar VATS segmentectomy for intra lobar pulmonary sequestration using indocyanine green for identification of the intersegmental plane: a case report entire lobe that is affected and a segmentectomy should be considered (3). I present the following case in accordance with the CARE reporting checklist (available at http:// dx.doi.org/10.21037/jovs-21-21).…”
Section: Case Reportmentioning
confidence: 99%
“…The ideal treatment of ILS would be the resection of the sequestered lung using segmentectomy and lobectomy [5], as in this case. However, this procedure could lead to prolonged air leakage [5], which may require reoperation for completion lobectomy or necessitated prolonged drainage of pleural cavity.…”
Section: Commentmentioning
confidence: 99%
“…The ideal treatment of ILS would be the resection of the sequestered lung using segmentectomy and lobectomy [5], as in this case. However, this procedure could lead to prolonged air leakage [5], which may require reoperation for completion lobectomy or necessitated prolonged drainage of pleural cavity. Simple ligation and arterial coiling embolization of the anomalous artery has also been used to eliminate symptoms in patients with type 1 ILS [6].…”
Section: Commentmentioning
confidence: 99%
“…An increasing evidence have indicated that minimally invasive video-assisted thoracic surgery has many advantages in the treatment of PS. Comparing with open surgery, thoracoscopy can clearly reveal the hilar area and aberrant feeding area; other indicators including blood loss, duration of chest tube insertion, postoperative hospital stay and complications also have a slight advantages (10)(11)(12)(13)(14). However, some difficulties still exist.…”
Section: Introductionmentioning
confidence: 99%